ANALYSIS OF ENERGY ABSORPTION CHARACTERISTICS OF AL-CFRP HYBRID TUBES UNDER QUASI-STATIC RADIAL COMPRESSION - ZHA YiBin; MA QiHua; ZHOU TianJun (Jixie qiangdu)
The quasi-static radial compression performance of carbon fiber reinforced plastic（CFRP） wound thin-walled aluminum tubes was studied by means of experimental research,theoretical and simulated analysis.Based on the joint action of aluminum and CFRP tubes,the theoretical model of initial failure load and total energy absorption of Al-CFRP hybrid tube under radial compression is established firstly.Then,the quasi-static radial compression experiment of Al-CFRP hybrid tube is carried out and the results show that the experimental results are in good accordance with the theoretical results which verifies the accuracy of the theoretical model that is carried on the supplementary improvement by finite element simulation.Based on the established theoretical model,the effects of winding angle of carbon fiber and the layer thickness ratio of aluminum tube and CFRP tube on initial failure load and total energy absorption of the hybrid tube were studied.The results show that the initial failure load and total energy absorption of the hybrid tube with a stable failure mode and bearing capacity are higher than those of the aluminum tube under quasi-static radial compression;The initial failure load and total energy absorption of the hybrid tube decrease first and then increase with the increase of the winding angle of carbon fiber and the thickness ratio of Al-CFRP layer.